A virtual resistor design method based on voltage harmonic amplification factor for active damper used in DFIG system. (December 2020) - Li, Fei; Liu, Yang; Xu, Ke; Ma, Mingyao; Zhang, Xing; Wang, Lingxiang
Abstract: When grid impedance cannot be ignored, high-frequency harmonic amplification often occurs when Doubly-Fed Induction Generator (DFIG) generation system is connected to a non-ideal grid with background noise. This paper analyzes the mechanism of high-frequency harmonic amplification of DFIG wind power generation system under non-ideal grid, and quantifies the damping through the equivalent RLC one-port impedance model. The concept of voltage amplification factor is proposed to guide the design of virtual resistor for harmonic suppression. Based on the design results, the virtual resistor is realized by an active damper connected in parallel with the DFIG system at the point of common coupling (PCC). Considering the limit of this device, this paper designs the lower limit of the virtual resistor in case of over-modulation problem. Finally, a controller hardware-in-the-loop experiment is carried out based on the RT-LAB platform, and the experimental results verified the correctness of the analysis and the effectiveness of the device.